Skin Cancer Associated Genodermatoses: A Literature Review - Juliane Schierbeck; Tine Vestergaard; Anette Bygum (Medical Journals Sweden, 2019)
Skin cancer has become the most common type of cancer worldwide as a result of environmental exposure and medical treatments. A small group of patients are genetically predisposed to skin cancer and this article is intended as a diagnostic tool when encountering patients with multiple skin cancer lesions. The disorders are described with clinical characteristics, genetics and management. The most common syndromes associated with basal cell carcinoma are: Gorlin-Goltz syndrome, Rombo syndrome, and Bazex-Dupré-Christol syndrome. Multiple squamous cell carcinomas can be related to: xeroderma pigmentosum, Ferguson-Smith, Muir-Torre syndrome, Mibelli-type porokeratosis, keratitis-ichthyosis-deafness syndrome, Rothmund-Thomson syndrome, Bloom syndrome, and epidermodysplasia verruciformis. Malignant melanoma can be inherited, as in familial atypical multiple mole melanoma syndrome.